2012
DOI: 10.2174/138920112802273218
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies and Sjogren’s Syndrome: A Physiologist’s Perspective

Abstract: Sjögren's syndrome is a systemic autoimmune condition centred around salivary gland dysfunction and atrophy. There are a plethora of antibodies that mark the decline of the salivary glands, most of which relate to apoptopic mediated destruction of acinar cells. The best known of these autoantibodies, anti-Ro and anti-La form part of the diagnostic criteria for the condition. An emerging viewpoint in recent years is that glandular dysfunction precedes rather than follows glandular atrophy and attention has shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Except for the anti-parotid secretory protein and anti-M3R antibodies, most autoantibodies target antigens that are normally present inside cells. Therefore, those autoantibodies reflect the apoptotic destruction of gland tissues, that is, a result of the disease process rather than the cause of the disease [ 10 ]. The degree of salivary dysfunction in SS patients does not correlate with the degree of glandular tissue destruction [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Except for the anti-parotid secretory protein and anti-M3R antibodies, most autoantibodies target antigens that are normally present inside cells. Therefore, those autoantibodies reflect the apoptotic destruction of gland tissues, that is, a result of the disease process rather than the cause of the disease [ 10 ]. The degree of salivary dysfunction in SS patients does not correlate with the degree of glandular tissue destruction [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The binding of autoantibodies to M3R also down-regulates the receptors from the plasma membrane by inducing internalization [ 33 ]. However, the functional data have not been reconciled with the sensitivity and specificity of the anti-M3R autoantibodies in screening trials [ 10 ]. Although anti-M3R autoantibodies have been detected in 9–100 % of SS patients depending on the method and antigens used [ 34 ], a recent meta-analysis study concluded that the anti-M3R antibody has high specificity (0.95) but relatively low sensitivity (0.43) to diagnose SS [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Passafaro et al showed that anti-M3R antibodies act as a partial muscarinic agonist, which increase prostaglandin E2 (PGE2) and cyclic AMP production through modifying Na + /K + -ATPase activity and also interfere with the secretory effect of the parasympathetic neurotransmitter [11]. Using muscle strip and whole organ functional assays, Smith and Dawson showed that IgG with anti-M3R activity from patients with SS disrupted neurotransmission in tissues throughout the mouse gastrointestinal tract [12]. Several researchers have selected the second extracellular loop as the crucial part involved in the progression of pSS since it is an epitope of anti-receptor antibodies for many G-protein coupled receptors in other autoimmune conditions.…”
Section: The Autoantibodiesmentioning
confidence: 99%
“…Despite the focal appearance of T cells in the salivary gland, however, B cell–deficient NOD.Igµ null mice required transfer of purified IgG from patients with SS to develop the loss of secretory function, indicating the role of autoantibodies in glandular dysfunction in SS (3). Although autoantibodies to type 3 muscarinic acetylcholine receptors identified in SS can interfere with the secretory process (45), the pathophysiology of glandular dysfunction in SS has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%